Erratum: KAREN E. UNDERKOFFLER, MEAGAN A. LUERS, JOHN R. HYDE & MATTHEW T. CRAIG (2018) A taxonomic review of Lampris guttatus (Brünnich 1788) (Lampridiformes; Lampridae) with descriptions of three new species. Zootaxa, 4413: 551–565. - Underkoffler, Karen E.; Luers, Meagan A.; Hyde, John R.; Craig, Matthew T. (Zootaxa, 2018)
N/A